Pelajaran bahasa Arab untuk Perguruan Tinggi Agama Islam/IAIN Tingkat lanjut [Advance]. - INDONESIA... (Departemen Agama, 1980)
ir, jil.1,c.1/en, jil.1=c.2-5; jil.2=c.1-5; jil.3=c.1-5; jil.4=c.1-6; jil.5=c.1-4